Relationship Between Depression and the Use of Mobile Technologies and Social Media Among Adolescents: Umbrella Review - Arias-de la Torre, Jorge; Puigdomenech, Elisa; García, Xavier; Valderas, Jose M; Eiroa-Orosa, Francisco Jose; Fernández-Villa, Tania; Molina, Antonio J; Martín, Vicente; Serrano-Blanco, Antoni; Alonso, Jordi; Espallargues, Mireia (JMIR Publications, 2020)
BackgroundDespite the relevance of mobile technologies and social media (MTSM) for adolescents, their association with depressive disorders in this population remains unclear. While there are previous reviews that have identified the use of MTSM as a risk factor for developing depression, other reviews have indicated their possible preventive effect. ObjectiveThe aim of this review was to synthesize the current evidence on the association between MTSM use and the development or prevention of depressive disorders in adolescents. MethodsAn umbrella review was conducted using information published up to June 2019 from PubMed/MEDLINE, PsycINFO, Web of Science, and The Cochrane Library. Systematic reviews focusing on the adolescent population (up to 20 years old) and depression and its potential relationship with MTSM use were included. Screening of titles, abstracts, and full texts was performed. After selecting the reviews and given the heterogeneity of the outcome variables and exposures, a narrative synthesis of the results was carried out. ResultsThe search retrieved 338 documents, from which 7 systematic reviews (3 meta-analyses) were selected for data extraction. There were 11-70 studies and 5582-46,015 participants included in the 7 reviews. All reviews included quantitative research, and 2 reviews also included qualitative studies. A statistically significant association between social media and developing depressive symptoms was reported in 2 reviews, while 5 reviews reported mixed results. ConclusionsExcessive social comparison and personal involvement when using MTSM could be associated with the development of depressive symptomatology. Nevertheless, MTSM might promote social support and even become a point of assistance for people with depression. Due to the mixed results, prospective research could be valuable for providing stronger evidence.